(untitled) (JULACE: Journal of the University of Namibia Language Centre, 2018)
This paper reports on the use of cooperative learning technique – Jigsaw - that describes the use of small groups to enable learners to increase their own responsibility in learning and that of their peers. As a strategy that support Learner Centred Education which was adopted as a framework for teaching and learning in Namibia in 1990, cooperative learning is very compatible to Communicative Language Teaching (CLT) which are both highlighted in the new basic education national curriculum as strategies for teaching languages in Namibian schools. To develop responsive practices to the learner-centred approach this study investigates the role of cooperative learning activities in learning English second language and the influence it has on teaching and assessing learners. An expansive route was taken to engage learners in a Jigsaw activity, in an English Second Language lesson. The findings revealed that participants of the study perceived cooperative learning instructional to be generally a positive experiences which provide an effective method of learning in groups and it enhance learners’ achievement. Cooperative learning may help learners to acquire and develop four language skills at the same time and with easy as concepts are interlinked. Learners in the jigsaw classroom reported stronger intrinsic motivation, greater interest in the topic, and more cognitive activation and involvement.